An infrared measurement of chemical desorption from interstellar ice analogues. (March 2018) - Oba, Y.; Tomaru, T.; Lamberts, T.; Kouchi, A.; Watanabe, N.
Abstract In molecular clouds at temperatures as low as 10 K, all species except hydrogen and helium should be locked in the heterogeneous ice on dust grain surfaces. Nevertheless, astronomical observations have detected over 150 different species in the gas phase in these clouds. The mechanism by which molecules are released from the dust surface below thermal desorption temperatures to be detectable in the gas phase is crucial for understanding the chemical evolution in such cold clouds. Chemical desorption, caused by the excess energy of an exothermic reaction, was first proposed as a key molecular release mechanism almost 50 years ago1 . Chemical desorption can, in principle, take place at any temperature, even below the thermal desorption temperature. Therefore, astrochemical network models commonly include this process2, 3 . Although there have been a few previous experimental efforts4–6, no infrared measurement of the surface (which has a strong advantage to quantify chemical desorption) has been performed. Here, we report the first infrared in situ measurement of chemical desorption during the reactions H + H2 S → HS + H2 (reaction 1) and HS + H → H2 S (reaction 2), which are key to interstellar sulphur chemistry2, 3 . The present study clearly demonstrates that chemical desorption is a more efficient process for releasing H2 S into the gas phase than was previously believed. The obtained effective cross-section for chemical desorption indicates that the chemical desorption rate exceeds the photodesorption rate in typical interstellar environments. The efficiency of the chemical desorption caused by the reactions between H2 S, HS and H on an icy grain surface analogue has been quantified by means of in situ infrared measurements of the surface, providing valuable information for understanding non-thermal desorption processes.